KEPUASAN PELAYANAN PELANGGAN DENGAN MENINGKATKAN KETERAMPILAN DAN KESADARAN MENTAL SUMBER DAYA MANUSIA - Abi Prasidi; Devi Marlita (Institut Transportasi dan Logistik Trisakti, 2015)
Human Resources Development is an organization's activities must be carried out, so that knowledge (knowledge), abilities (abilities) and skills (skills) they are in accordance with the demands of the job they do. In the field of services, especially transportation, in truth, in this section should be special attention which both the management and the employees have the mental awareness to focus, concentrate, development and innovate, given the mental attitude has to be in good condition, sometimes, can easily fade back.